Level of Student Involvement: Judging from Self-Efficacy and Peer Conformity - Pramesti, Febiyani Setya; Raharjo, Trubus (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to empirically test the relationship between Self Efficacy and Peer Conformity and Student Engagement. The population of this study were students of SMA Muhammadiyah Purwodadi class X and XI. The sampling technique used was Quota Sampling with research subjects totaling 217 students. The data analysis method used by Pearson correlation is regression of two predictors and product moment. The results of the major hypothesis test obtained a correlation coefficient rx12, y of 0.235 with a significance level of p = 0.002 (p<0.01) which means there is a significant relationship between Self Efficacy and Peer Conformity with Student Engagement with an effective contribution of 5.5%. The results of the analysis of the first minor hypothesis obtained rx1y of 0.055 with a significance level of p = 0.00 (p<0.05), which means there is a very significant relationship between Self Efficacy and Student Engagement with an effective contribution of 5.5%. Meanwhile, for the results of the second minor hypothesis, an rx2y correlation coefficient of 0.002 was obtained with a significance level of p = 0.273 (p>0.05), which means that there is no relationship between Peer Conformity and Student Engagement, which can also mean that the hypothesis is rejected.